Diagnosis of Coronary Heart Disease by Using Hybrid Intelligent Systems Based on the Whale Optimization Algorithm, Simulated Annealing and Support Vector Machine - Zeinab Hassani; Mahin Khosravi (مدیریت مهندسی و رایانش نرم)
In recent years, machine learning algorithms are widely used for diagnosis and timely treatment of diseases. Moreover, diagnosis of disease on early stages is very effective in improving the disease and in reducing the cost of treatment for the patient. Heart disease is one of the main causes of death in the world. Several studies have been conducted to diagnose of disease and to design an intelligent and efficient system. In this paper, a hybrid algorithm of Whale Optimization Algorithm and simulated annealing are presented to identify the effective factors in the diagnosis of the disease. The support vector machine algorithm is considered for effective classification of the disease. The proposed approach is evaluated using the Cleveland Heart Disease Data Collection in the UCI database. The proposed algorithm has obtained with an accuracy of 87.78% which is able to diagnose of disease with fewer attributes. The results exhibition the superiority of the proposed method which the proposed approach can help physicians to diagnose and to improve disease in the early stages